Prediction of vapor-liquid equilibria of binary mixtures using quantum calculations and activity coefficient models - Tat, Pham Van (Vietnam Journal of Chemistry, 2014)
In this work, the conductor-like screening model COSMO-SAC (segment activity coefficient) obatained from the density functional theory calculations DFT-VWN-BP with basis set DNP (double numerical basis set augmented with polarization function). The molecular-single sigma profiles were generated by using COSMO calculations. The vapor-liquid equilibria (VLE) for three binary mixtures water(1) - ethanol(2), methanol(1) - benzene(2) and toluene(1) - chlorobenzene(2) were calculated from these sigma profiles. The VLE data of these mixtures turn out to be in good agreement with experimental data as far as such data resulting from the activity coefficient models Wilson [1] and NRTL (non-random two-liquid) [2]. RMS error, mean relative deviation of pressure (MRDp) and mean deviation of vapor composition (MDy) are less than 0.087, 9.052 and 0.065, respectively. Keywords: Vapor-liquid equilibria, conductor-like screening model COSMO-SAC.